A Systematic Bibliometric Review of Cultural Heritage Conservation Research - Judijanto, Loso; Malik, Abdul Hadi (Eastasouth Institute, 2025)
This study does a comprehensive bibliometric analysis of international research on cultural heritage preservation from 2000 to 2025, utilizing data from Scopus and Web of Science. We used VOSviewer and Bibliometrix (R package) to do a bibliometric study that showed publishing patterns, research themes, and collaboration networks. The results indicate that the discipline has transitioned from conventional preservation methods to sustainability-focused and technology-driven conservation. Heritage conservation, historic preservation, sustainable development, and urban planning are some of the main issues. Newer fields include preventive conservation, digital heritage recording, and adapting to climate change. Europe, especially Italy and Spain, is the most productive region for research, but China, Australia, and Latin America are also contributing more. The visualizations show that conservation research, environmental preservation, and cultural tourism are becoming more connected across disciplines. The paper offers a thorough examination of the intellectual framework of the profession and emphasizes the transition towards data-driven, sustainable, and internationally collaborative methodologies in cultural asset conservation.